The Taxation of Petroleum and Minerals : Principles, Problems and Practice. (International Monetary Fund, 2010)
There are few areas of economic policy-making in which the returns to good decisions are so high-and the punishment of bad decisions so cruel-as in the management of natural resource wealth. Rich endowments of oil, gas and minerals have set some countries on courses of sustained and robust prosperity; but they have left others riddled with corruption and persistent poverty, with little of lasting value to show for squandered wealth. And amongst the most important of these decisions are those relating to the tax treatment of oil, gas and minerals. This book will be of interest to Economics postgraduates and researchers working on resource issues, as well as professionals working on taxation of oil, gas and minerals/mining.